Can constructive deviance be empowered? A multi-level field study in Australian supermarkets. (May 2020) - Mertens, Willem; Recker, Jan
Abstract: We test four hypotheses about how leaders facilitate constructive deviance in the teams they manage. Constructive deviance describes ways of creating value by departing from common ways of working. We test a multi-level model that suggests links between various leadership behaviors, psychological empowerment, and constructive deviance at the individual and team levels. Our findings add nuance to the prevalent assumption that empowered employees engage in more constructive deviance than unempowered employees do by suggesting that, rather than stimulating constructive deviance, empowerment makes deviance unnecessary. We detail implications for management.